End-of-Life Care Issues: A Personal, Economic, Public Policy, and Public Health Crisis - Morhaim, Dan K. (American Public Health Association, 2013)
Advance directive documents are free, legal, and readily available, yet too few Americans have completed one. Initiating discussions about death is challenging, but progress in medical technology, which leads to increasingly complex medical care choices, makes this imperative. Advance directives help manage decision-making during medical crises and end-of-life care. They allow personalized care according to individual values and a likely reduction in end-of-life health care costs. We argue that advance directives should be part of the public health policy agenda and health reform.